The Effectiveness of Group Counseling in Increasing Children’s Confidence - Dina Indriani; Nurhayani Nurhayani (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine the effectiveness of group counseling in increasing children's self-confidence in the Al Wasliyah Charitable Foundation Orphanage, Gedung Johor with the design concept of One-Group Pretest-Posttest design. The sample was 14 orphanage children consisting of junior high and high school levels who had low self-confidence. In collecting questionnaire data, the results of the research achieved provide positive results, guidance services can increase student confidence, this can be seen from the results of Pre-test and Post-test p = 0.000, namely: p <; 0.05, it is concluded that Ho was rejected and Ha was accepted, meaning that in addition to the mean after testing greater than the value before testing (83.0 ≥ 79), it can be believed that group counseling is effectively used to increase the confidence of class children at the Al Wasliyah Charitable Foundation Orphanage Johor Building.